Neighbourhood built environment and walking behaviours: Evidence from the rural American South. Issue 7 (August 2018) - Li, Chuo; Chi, Guangqing; Jackson, Robert
This study examines the perceived neighbourhood characteristics and environmental barriers in association with two different types of walking – recreational and destination – in the context of a rural town in Mississippi. A cross-sectional survey was used to assess residents' walking behaviours, perceived neighbourhood characteristics and perceived environmental barriers to walking in three types of neighbourhoods: traditional, early conventional suburban and late conventional suburban. Descriptive statistics, one-way analysis of variance and regression analyses identified environmental factors correlated with walking. A total of 362 surveys were completed and returned by random adult members of the households contacted, for a 38.5% response rate. Perceived aesthetics are significantly associated with more frequent recreational and destination walking in this rural town. Higher perceived accessibility are associated with more frequent destination walking, and greater perceived social environment barriers to walking are associated with sedentary behaviour in the rural population studied. Of all factors related to a neighbourhood's built environment, the most important factor in promoting walking in rural towns is aesthetics. The relationships among accessibility, social environment and walking underscore the importance of community planning in incorporating mixed land uses, providing a connected pedestrian infrastructure and facilitating targeted social interventions to encourage more walking.